The prognostic value of fibrinogen to albumin ratio in malignant tumor patients: A meta-analysis - Baibei Li; Huachu Deng; Biao Lei; Leijie Chen; Xinyuan Zhang; Dingran Sha (Frontiers in Oncology, 2022)
BackgroundRecent studies have shown that the fibrinogen to albumin ratio (FAR) is closely related to the prognosis of various cancers. The aim of this systematic review and meta-analysis was to investigate the prognostic value of FAR in malignancies based on the available evidence.MethodTo systematically search the Cochrane Library, Embase, PubMed, Google Scholar, Baidu scholars, CNKI and VIP databases for relevant studies published before April 1, 2022, and to evaluate the fibrinogen-to-albumin ratio (FAR) and survival of patients with malignant tumors through a meta-analysis relationship between the results. Results. This meta-analysis included 19 eligible studies involving 5926 cancer patients. We found that high FAR was associated with poor overall survival (HR=2.25, 95%CI 1.86-2.74, p<0.001), recurrence-free survival (HR=2.29, 95%CI 1.91-2.76, P<0.001), progression-free survival (HR: 2.10, 95%CI 1.58-2.79, p<0.001), disease-free survival (HR=1.52, 95%CI 1.17-1.96, p=0.001), and time to recurrence (HR: 1.555, 95%CI 1.031-2.346, P=0.035) was significantly correlated.ConclusionsHigh FAR is significantly associated with poor clinical outcomes in cancer, suggesting that it may be an important predictor of prognosis in patients with malignancies.